PkM Metode Story Telling Berbantuan Hand Puppet dalam Mengasah Keterampilan Berbahasa dan Pemahaman Moral pada Anak - Deni Ramdani; Rifka Agustianti (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
Children's low language skills and moral understanding pose a challenge for parents. Furthermore, their low interest in reading is a key focus of this activity. An engaging method is needed to encourage children to listen and understand a story. Therefore, a solution is needed to address this issue, namely through storytelling activities using hand puppets for children aged kindergarten through third grade. In this activity, an inspirational story is told so that children can learn the moral values contained within the story. Then, they retell the story using homemade hand puppets to hone their language skills. This activity aims to hone language skills for public storytelling, provide an alternative learning method for instilling morals in children through creative and fun media, provide space for children to be creative in making simple hand puppets and displaying them in public, and build children's self-confidence. Evaluation of the community service activity was conducted at the end of the activity using a questionnaire, and the results were summarized using pre-test and post-test assessments.